2014
DOI: 10.1042/bst20140137
|View full text |Cite
|
Sign up to set email alerts
|

Substrate trajectory through phospholipid-transporting P4-ATPases

Abstract: A difference in the lipid composition between the two leaflets of the same membrane is a relatively simple instance of lipid compositional heterogeneity. The large activation energy barrier for transbilayer movement for some (but not all) membrane lipids creates a regime governed by active transport processes. An early step in eukaryote evolution was the development of a capacity for generating transbilayer compositional heterogeneity far from equilibrium by directly tapping energy from the ATP pool. The mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Like other P-type ATPases, P4-ATPases contain a large catalytic or α-subunit composed of a nucleotide binding domain (N-domain), a phosphorylation domain (P-domain), and an actuator domain (A-domain) which are involved in the ATP reaction cycle, and a membrane domain (M-domain) consisting of 10 predicted transmembrane segments which serve as the pathway for the translocation of phospholipids across cell membranes 1 , 17 21 . In addition, some mammalian P4-ATPases contain an extended C-terminal segment implicated in protein folding and regulation of its activity 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Like other P-type ATPases, P4-ATPases contain a large catalytic or α-subunit composed of a nucleotide binding domain (N-domain), a phosphorylation domain (P-domain), and an actuator domain (A-domain) which are involved in the ATP reaction cycle, and a membrane domain (M-domain) consisting of 10 predicted transmembrane segments which serve as the pathway for the translocation of phospholipids across cell membranes 1 , 17 21 . In addition, some mammalian P4-ATPases contain an extended C-terminal segment implicated in protein folding and regulation of its activity 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Another puzzling feature of this model is that TM5 is situated behind TM4 and is clearly separated from the water-filled cavities, since previously obtained experimental evidence for ATP8A2 demonstrated that a specific conserved lysine residue in TM5 is essential for phospholipid translocation 7 . An alternative theoretical model has been recently proposed based on the plasma membrane H + -ATPase structure 11 . This theoretical model suggests that a water-filled cavity exists in P4 ATPases that is analogous to the one in the crystal structure of H + -ATPases, between TM4, TM5, and TM6.…”
Section: Introductionmentioning
confidence: 99%
“…As recently outlined [47], the phospholipid substrate trajectory through P4-ATPases is yet poorly understood and under careful investigation. On the basis of the present study, a plausible hypothesis is that the CDC50 proteins are located near the transport pathway and participate in the transport mechanism.…”
Section: Discussionmentioning
confidence: 99%